A visão de professores surdos sobre o processo de produção de materiais didáticos para o ensino de libras para ouvintes no formato de vídeos - Silva, Cleidiane Alves da (2023)
Thisresearch proposal which theme is : The production of videos by deaf teachersin the production of didactic material for the teaching of Libras to listeners. It aims to analyze the view of deaf teachers of the Libras courses offered at Centro de Capacitação de Profissionais da Educação e de Atendimento às Pessoas com Surdez de Goiânia-Goiás (CASGoiânia) on the process of production of didactic material for the teaching of Libras in the format of videos, and its limits and possibilities. The research has a qualitative approach, of the exploratory type, since this makes it possible to obtain in a more significant way, the objectives of the research for the suggestion of new pedagogical procedures. As methodological procedures, bibliographic research and field research are adopted, with interviews with deaf teachers who teach at CAS-Goiânia. The theoretical framework is composed by the authors: Gesser (2006, 2009,2012), Medeiros and Gräff (2012), Gomes and Basso (2014), Lacerda (2009) and Segalla (2010), among others, with reflections on deaf culture, Libras, teaching of Libras and didactic material. As a result, it was identified that the vision of deaf teachers includes: videos need to have images; it is important to have subtitles in Portuguese; the use of stories so that Libras is contextualized; there are some difficulties with the Portuguese during the video production process; And different types of technologies are important for them to be able to produce good materials.